An analysis of competitiveness of the EU countries using the dependent mixture model - Genge, Ewa (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
As European Union countries are facing particularly difficult economic management decisions with challenging political and social ramifications, we try to find groups of countries which face a similar challenge of improving their competitiveness indicators. We focus on the dependent mixture model which additionally allows us to investigate the dynamic pattern of the competitiveness index and pillars organized into three sub-indices time series. This methodology will provide an opportunity to investigate which countries feature a similar level of competitiveness stability (are able to sustain their level of competitiveness) and which have similar regime-switching propensities. These results may contribute to the current policy discussion on measures for achieving the sustainable competitiveness of the European Union economies, EU strategy and reform programmes in separate member states
Argumenta Oeconomica, 2017, Nr 2 (39), s. 111-128
Keywords: competitiveness; latent Markov models; dependent mixture model; EU countries